Effects of hesperidin and ascorbic acid combination on boar sperm quality during cryopreservation - Ruilan Dong; Yupeng Dou; Min Zhang; Lan Luo; Guanghui Yu (Frontiers in Veterinary Science, 2025)
Hesperidin or ascorbic acid is an effective antioxidant that can protect frozen-thawed sperm from oxidative damage. The aim of the present study was to investigate the cryoprotective effects of hesperidin (Hsd) and ascorbic acid (AsA) on boar sperm quality during cryopreservation. Sperm samples were collected once a week for 3 weeks. The ejaculated semen from eight boars in each of three replicates were pooled and split into seven groups with different doses of Hsd (0, 15, 45) μM and/or AsA (0, 100, 300) μM added to the freezing extender. The sperm motility, membrane integrity, acrosome integrity, mitochondrial membrane potentials, DNA integrity, reactive oxygen species (ROS), malondialdehyde (MDA) concentration, antioxidant enzyme activities, and protein expression were measured after freezing-thawing to evaluate the qualitative parameters of boar sperm. The results showed that the sperm motility, plasma membrane integrity, acrosomal integrity, DNA integrity, and mitochondrial membrane potential were significantly improved in the 15 μM Hsd + 100 μM AsA group compared with the control and other treatment groups (p < 0.01). It was observed that the supplementation in the 15 μM Hsd + 100 μM AsA group significantly improved the ATP content and antioxidant enzyme activities (SOD, CAT, GSH-Px, and PRODH) (p < 0.01). The levels of MDA and ROS were significantly reduced in the 15 μM Hsd + 100 μM AsA group (p < 0.01). Moreover, the supplementation of Hsd combined with AsA significantly increased the expression of the anti-apoptosis protein Bcl-2 and decreased the expression of the pro-apoptotic protein caspase-3, P53, Bax, and Cytochrome C (p < 0.05). These findings demonstrated that supplementing the freezing extender with both Hsd and AsA had a combined, beneficial effect on the quality of frozen-thawed boar sperm. The combination of 15 μM Hsd + 100 μM AsA showed greater potential in protecting the boar sperm during cryopreservation than the separate addition of either Hsd or AsA. The supplementation of Hsd and AsA could improve the quality of frozen-thawed sperm as an antioxidant.